THU0002 Pathological Findings Using High END Ultrasonography in Primary SjÖGren's Syndrome. (10th June 2014) - Hofauer, B.; Bas, M.; Mansour, N.; Knopf, A.
Abstract : Background: During the last years there have been numerous reports and discussions concerning the diagnostic value of ultrasonography of salivary glands for assessment of salivary gland involvement in patients suspected with primary Sjögren's Syndrome (pSS). Modern ultrasound techniques, such as acoustic radiation force impulse (ARFI) imaging, real time tissue elastography (RTTE) and virtual touch tissue imaging (VTTI), could gain in importance lately and became part of the clinical routine in various specialties. Objectives: Can modern ultrasound techniques provide further information in the assessment of salivary gland involvement in patients suspected with pSS in addition to B-mode ultrasonography (BMUS)? Methods: The diagnostic value of modern ultrasound techniques was evaluated in 50 patients with pSS, diagnosed according to the AECG criteria. Patients underwent high-resolution ultrasonography (THI, 9-14 MHz) of the parotid and submandibular gland. Results of BMUS, RTTE, VTTI – each graded by using appropriate ultrsonographic scoring systems – and ARFI quantifications were compared to 50 patients with sicca symptoms but not fulfilling the AECG criteria. Results: In BMUS, 41/50 parotid glands in patients with pSS and 20/50 in the control group had abnormal findings (p<0.001). 42/50 patients with pSS showed abnormal findings in submandibular gland BMUS compared to 31/50 in patients without confirmed pSS (p<0.001). Evaluation of parotid and submandibular RTTE did not show any difference (p=1.0 and p=0.06), nor did the evaluation of parotid and submandibular VTTI (p=0.251 and p=0.835). ARFI imaging of the parotid (mean: 2.99m/s 2 ) and submandibular glands (mean: 2.54m/s 2 ) showed significant higher values than parotid (mean: 2.16m/s 2 ) and submandibular glands (mean: 2.04m/s 2 ) in the control group (p<0.001 and p=0, 008). Conclusions: In contrast to B-mode ultrasonography in patients suspected with primary Sjögren's Syndrome, which is proved to be useful in visualization and subjective assessment of structural glandular alterations, ARFI imaging enables the objective measurement of glandular stiffness and might therefore be considered in the diagnostic algorithm of pSS. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5901